2010
DOI: 10.1270/jsbbs.60.405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cleistogamy on Fusarium head blight resistance in wheat

Abstract: In wheat (Triticum aestivum L.), Fusarium head blight (FHB) resistance is an important breeding target to reduce yield losses and mycotoxin contamination. We hypothesized that cleistogamous (CL, closed flowering) cultivars have a lower risk of FHB infection than chasmogamous (CH, opened flowering) cultivars because FHB infection usually occurs in the inside of florets or extracted anthers and FHB resistance in CL cultivars decreases mycotoxin accumulation. To test these hypotheses, we produced 126 recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
7
31
0
Order By: Relevance
“…This is can be attributed at least partially to the progress of stress caused by R. secalis infection on susceptible barley which might lead plants to activate this kind of genes for their reproduction. This is in agreement with the results of Kubo et al (2010) a bout the basic role of this gene towards fungus.…”
Section: Discussionsupporting
confidence: 93%
“…This is can be attributed at least partially to the progress of stress caused by R. secalis infection on susceptible barley which might lead plants to activate this kind of genes for their reproduction. This is in agreement with the results of Kubo et al (2010) a bout the basic role of this gene towards fungus.…”
Section: Discussionsupporting
confidence: 93%
“…This resistance is one of two major categories of resistance to FHB: resistance to initial infection (Type I), and resistance to pathogen spread in infected tissue (Type II) (Shroeder and Christensen 1963). Our results are in agreement with those of Kubo et al (2010Kubo et al ( , 2013 who found the severity of FHB infection in cleistogamous (closed flowering) recombinant inbred lines (RILs) and double haploid lines (DHLs) of wheat to be significantly lower than in chasmogamous (opened flowering) RILs and DHLs, hence demonstrating that the closed-flowering (no anther extrusion) characteristic was effective in increasing resistance to FHB infection. In their experiments, the lines set seed, hence seed set did not affect disease severity (as may have occurred in our experiments).…”
Section: Discussionsupporting
confidence: 92%
“…Later studies have also highlighted the importance of anther extrusion. Kubo et al (2010) found that cleistogamous lines initially had reduced FHB infection, but chasmogamous lines were not different for kernel shriveling or mycotoxin levels. Furthermore, Kubo et al (2013) found minor differences in anther extrusion affected FHB resistance in wheat.…”
Section: Introductionmentioning
confidence: 85%
“…To investigate the accumulation of mycotoxins of selected materials, we performed randomized block field experiments in the experimental fields 19,20 . Before sowing, the soil was fertilized with 30 kg ha -1 N, 26 kg ha -1 P 2 O 5 , and 26 kg ha -1 K 2 O. Twenty seeds of each materials were sown 70 cm apart in a row.…”
Section: Fusarium Damaged Kernels and Mycotoxin Accumulationmentioning
confidence: 99%